Living on the slum areas in the shadow of drought: a qualitative analysis of lived experience of migrant households facing drought in Southeast of Iran - Minoo Mohammadkhani; Nouzar Nakhaee; Reza Goudarzi; Mahmood Nekoei-Moghadam; Mohsen Aminizadeh (BMC, 2024)
Abstract Background Drought is one of the most destructive and complex natural hazards, with direct and indirect effects, especially economic effects, on society and households. It affects the well-being and life satisfaction of households. It is important to understand the effects of drought at the micro level, such as households, by examining different attitudes, perceptions, and experiences of drought and its impacts. Methods This research aims to investigate the understanding and experiences of the residents of the poor areas of Kerman city regarding drought and its consequences on their well-being and life satisfaction. To that end, the descriptive phenomenology qualitative method was used, selected samples purposefully, and conducted semi-structured and in-depth interviews with households in August and September 2022. MAXQDA2020 software was used to manage and organize the data. Results From the analysis of the results of the interviews with the households, it was shown that the drought, with its impact on the economic, social, family, health, and environmental dimensions, has been identified as five main themes, leading to a decrease in the well-being and life satisfaction of the households. Conclusion The drought has caused the migration of families from the cities and villages around Kerman province to the outskirts of the city. Subsequently, with the increase in the population in the outskirts of the city, the problem of waterlessness has increased. As a result, the welfare and life satisfaction of households have decreased.